SAND DUNE CONSERVATION ZONE BASED ON TSUNAMI INUNDATION HAZARD IN PARANGTRITIS COASTAL AREA, BANTUL REGENCY, YOGYAKARTA SPECIAL PROVINCE : Remote Sensing and Geographic Information System A pplication - , RATIH FITRIA PUTRI, S.Si., Dr. rer.nat. Djati Mardiatno, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Tsunami waves occurred in the South Java Coastal Area and destructed the coastal area of West Java, Central Java, and DIY Province. Sand dune in Parangtritis coastal area has a function such as a barrier to threat tsunami hazard. Remote sensing technology and Geographic Information System become one of data source, in particular like Disaster Information Sy stem. he objectives of this research are: (1) To make spatial distribution of tsunami inundation hazard using Remote Sensing & GIS application (Direction wave), (2) To make Tsunami Inundation Scenario Hazard based on the Tsunami events in the Parangtritis Coastal Area using distance and friction map function. (E levation inundation scenario wave ), (3) To make Sand dune zone mapping using topographic data map analysis, and (4) To make sand dune conservation zone based on distribution tsunami inundation hazard zone and coastal regulation zone analysis. Sand dune conservation zone mapping will be correlated with coastal regulation zone in Parangtritis coastal area, Determination of the sand dune conservation zone has purpose to optimize sand dune function as a barrier tsunami inundation hazard. CRZ-I are ecologically sensitive areas where activities are largely prohibited ( explicitly mandates the protection of sand dunes). CRZ-II are developed areas for agriculture land cultivation. CRZ-III comprise all rural areas as well as undeveloped areas in urban limits. The result of this research are: (1) Tsunami inundation zone with southeast wave direction scenario, it can to determination area for sand dunes area will be conserved, such as CRZ I approximately 362.100 hectares (87.12%), CRZ II approximately 53.217 hectares (12.80%) and CRZ III approximately 0.307 hectares (0.07%)